Steatosis and NASH in type 2 diabetes - Hu, Mengyue; Phan, Franck; Bourron, Olivier; Ferré, Pascal; Foufelle, Fabienne (Biochimie, 2017)
Non Alcoholic Fatty Liver Disease (NAFLD) is currently the most common chronic liver disease in the world, encompassing various conditions ranging from simple steatosis, steatohepatitis, to fibrosis and cirrhosis. The association between NAFLD and Type 2 Diabetes (T2D) is strong and complex, given that the prevalence of NAFLD is particularly high in individuals with Type 2 Diabetes. In fact, insulin resistance occurring in this metabolic disease can promote NAFLD development, and vice versa, NAFLD can enhance insulin resistance. In this review, we focus on the mechanisms linking NAFLD and T2D, including fatty acid accumulation, inflammation, oxidative stress etc. We also discuss about situations showing a dissociation between steatosis and insulin resistance, in order to provide new insights for NAFLD therapeutic targets. •Steatosis and NASH are frequent among type 2 diabetic individuals.•In NAFLD patients, an increased dose of injected insulin is often necessary.•Insulin resistance promotes NAFLD through induced hepatic lipogenesis and adipose tissue lipolysis.•NAFLD enhances insulin resistance by inducing lipotoxicity, inflammation and ROS production.•Specific intrahepatic lipid species are important for alteration of insulin sensitivity.